Conceptualising and contesting ‘fast policy’ in teacher learning: a comparative analysis of Sweden, Finland and Australia - Hardy, Ian; Heikkinen, Hannu; Olin, Anette (Teacher Development, 2020)
In this article, the authors refer to key national policies, and associated politics, in the Swedish, Finnish and Australian contexts, to reveal the key discourses that characterise how ongoing teacher learning is constituted in these settings. Drawing upon Peck and Theodore’s notion of ‘fast policy’, the authors identify what they describe as the ‘markers’ of fast policy in relation to teachers’ continuing professional learning, at the same time as they indicate countervailing praxis-oriented discourses that challenge these ‘fast policy’ approaches. Their research reveals a complex picture, indicating the clear prevalence of such markers in the Australian context, recent challenges to such markers in the Swedish context, and less evidence of such markers in the Finnish context but with some anomalies more recently. The research presents contestation to such markers as resources for hope, at the same time as it cautions how various markers of fast policy exert influence on teachers’ learning.
Keywords: Educational policy; educational politics; fast policy; teacher professional development; teacher professional learning